Integrative treatment of hypertension [ a clinical and mechanistic approach - Blush, Joel A. (CRC Press, 2014)
"This book provides practical hands-on advice on the use of alternative methods of hypertension treatment. It describes mechanisms of high blood pressure and hypertension, common causes of hypertension, and standard medications used to treat the disease and their side effects. The book details alternative methods of treating hypertension, emphasizing their mechanisms of action, similarities to standard medications, and practical implementation advice. Finally, it outlines guidelines for blood pressure goals, categorizes each treatment as medicine or alternative, and suggests ways of implementing an integrative approach to hypertension treatment"